Surveys in Geophysics - Surveys in Geophysics (Springer Nature, 2026)
Surveys in Geophysics publishes refereed overview articles on physical, chemical and biological processes occurring within the Earth, on its surface, in its atmosphere and in the near-Earth space environment, including relations with other bodies in the solar system. Observations, their interpretation, theory and modeling are presented in relation to relevant disciplines in the Geosciences and related areas.
FI 1.09
Q1
Keywords: Earth; Space & Environmental Sciences; Geology & Geophysics; Geología; Geofísica; Acuerdos transformativos; Transformative agreements; Tierra sólida; Geodesia; Océanos; Atmósfera; Meteorología; Hidrología